Wild birds and avian influenza : (Food and Agriculture Organization of the United Nation, 2007)
The highly pathogenic avian influenza H5N1 strain has spread from domestic poultry to a large number of species of free-ranging wild birds, including non-migratory birds and migratory birds that can travel thousands of kilometres every year. The regular contact and interaction between poultry and wild birds has increased the urgency of understanding wild bird diseases. This manual contains chapters on the basic ecology of avian influenza and wild birds, capture and marking techniques (ringing, colour marking and satellite telemetry), disease sampling procedures, and field survey an monitoring procedures